Cienfuegos and the poetic projection of «Nicasio» - Monroe Z. HAFTER (Cuadernos Dieciochistas, 2011)
This article proposes a reading of Cienfuegos’ lyric poetry based on the existence of two levels of discourse, public and private, similar to the ones that can be differentiated in his plays and that the author cultivates with different purposes in mind. it is observed that cienfuegos wrote his poetry from a personal distance which nonetheless reflects his own life experience.